The boundaries of the criminal law - Duff, Antony (Oxford : Oxford University Press, 2010)
This is the first book of a series on criminalization, examining the principles and goals that should guide what kinds of conduct are to be criminalized, and the forms that criminalization should take. This volume studies the scope and boundaries of the criminal law, asking what principled limits might be placed on criminalizing behaviour.
Series statement on jacket.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Criminal law